PERAN KKN MUBALIGH HIJRAH UMBENGKULU DALAM MENINGKATKAN PEMAHAMAN KEAGAMAAN - Elvira; Noti Hajelaherea; Rika Oktavia; Aan Zulyanto (Universitas Muhammadiyah Bengkulu, 2026)
The KKN Mubaligh Hijrah program is a form of community service carried out by students of the University of Muhammadiyah Bengkulu at the Al-Firdaus Mosque, Kandang Limun Village, Bengkulu City, during the month of Ramadan. This study aims to analyze the role of the program in improving children's religious understanding. The method used in this study is a qualitative approach with data collection techniques in the form of observation, interviews, and documentation during the activity process. The results show that the KKN Mubaligh Hijrah program has a positive impact on improving children's religious understanding, which is characterized by increased ability to read the Qur'an and understanding of worship procedures, as well as changes in more religious behavior. In addition, students act as facilitators and role models in religious learning, and successfully revitalize the function of the mosque as a center for non-formal education. Thus, this program is effective in fostering children's religious understanding and character during the month of Ramadan. Keywords: children, KKN Mubaligh Hijrah, mosque, religious understanding, Ramadhan